LEGAL PROTECTION FOR THE FAMILIES OF TERRORISM CRIMINAL SUSPECTS - Yeni Nuraeni; Lasmin Alfies Sihombing (Jurnal Scientia, 2023)
Terrorism is an extraordinary crime that has crossed national borders and is an extraordinary crime. In cases of eradicating criminal acts of terrorism, Special Detachment 88 sometimes does not hesitate to kill someone suspected of being a terrorist. This act clearly violated human rights and violated the rights of the suspect regulated in the Criminal Code. This study aims to determine the rights of families of perpetrators of terrorism in accordance with the principle of protecting human rights, as well as to determine the effectiveness of pretrial institutions in providing protection to families of perpetrators of terrorism. The research method used is descriptive analytical normative with a juridical research specification approach. The results of the study illustrate that legal aid is an important instrument in the criminal justice system because it is an embodiment of the protection of human rights. In Law no. 39 of 1999 concerning Human Rights guarantees that everyone has the right to freedom from enforced disappearance and loss of life. It was concluded that the Human Rights Law to protect the rights of the families of terrorist suspects and pretrial has not been effective enough to protect the rights of suspects, defendants or families of suspected perpetrators of terrorism in carrying out law enforcement efforts during investigations. disappearances, arrests and detentions and beatings leading to death.